Write a business plan ... in no time - Fiore, Frank, 1946- (In no time., 2005)
It is a book for readers starting a small business and need to write a business plan but don't have time to waste. The reader is taken step-by-step writing a business plan using easy-to-follow to-do lists-from determining the type of plan needed to what the various pieces of the plan should be and common mistakes to avoid. The author also includes sample business plans that will clearly illustrate the best language and approach depending on the purpose of the plan. The to-do lists and step-by-step instructions in Write a Business Plan In No Time are the most effective and efficient solution for these busy entrepreneurs, allowing them to write a business plan the In No Time way-fast, simple, easy.